Defining the combinatorial space of PKC:CARD‐CC signal transduction nodes. (1st September 2020) - Staal, Jens; Driege, Yasmine; Haegman, Mira; Kreike, Marja; Iliaki, Styliani; Vanneste, Domien; Lork, Marie; Afonina, Inna S.; Braun, Harald; Beyaert, Rudi
Abstract : Signal transduction typically displays a so‐called bow‐tie topology: Multiple receptors lead to multiple cellular responses but the signals all pass through a narrow waist of central signaling nodes. One such signaling node for several inflammatory and oncogenic signaling pathways is the CARD‐CC/BCL10/MALT1 (CBM) complexes, which get activated by protein kinase C (PKC)‐mediated phosphorylation of the caspase activation and recruitment domain (CARD)‐coiled‐coil domain (CC) component. In humans, there are four CARD‐CC family proteins (CARD9, CARD10, CARD11, and CARD14) and 9 true PKC isozymes (α to ι). At this moment, less than a handful of PKC::CARD‐CC relationships are known. In order to explore the biologically relevant combinatorial space out of all 36 potential permutations in this two‐component signaling event, we made use of CARD10‐deficient human embryonic kidney 293T cells for subsequent pairwise cotransfections of all CARD‐CC family members and all activated PKCs. Upon analysis of NF‐κB‐dependent reporter gene expression, we could define specific PKC::CARD‐CC relationships. Surprisingly, as many as 21 PKC::CARD‐CC functional combinations were identified. CARD10 was responsive to most PKCs, while CARD14 was mainly activated by PKCδ. The CARD11 activation profile was most similar to that of CARD9. We also discovered the existence of mixed protein complexes between different CARD‐CC proteins, which was shown to influence their PKC response profile. Finally, multiple PKCs were found to use a common phosphorylation site to activate CARD9, while additional phosphorylation sites contribute to CARD14 activation. Together, these data reveal the combinatorial space of PKC::CARD‐CC signal transduction nodes, which will be valuable for future studies on the regulation of CBM signaling. Abstract : CARD‐CC/BCL10/MALT1 signaling complexes are activated by PKC‐mediated phosphorylation in response to specific upstream signals, leading to NF‐κB‐dependent gene expression. The caspase activation and recruitment domain (CARD)‐coiled‐coil domain (CC) family consists of four members and the PKC family of 9 members (subdivided in conventional, novel, and atypical subclasses). Here, we investigate the possible functional interactions between each specific PKC and CARD‐CC family member.